Projetos políticos, autoritarismo e exclusão nas comemorações da Independência do Brasil: Centenário (1922), Sesquicentenário (1972) e Bicentenário (2022) - João Paulo Pimenta; Janaina Martins Cordeiro (Cahiers des Amériques Latines)
This article analyses aspects of Brazilian collective memory related to civic rituals. More specifically, those concerned to the history of Brazilian Independence. Three moments are focused here: the Centenary (1922), the Sesquicentennial (1972) and the Bicentenary (2022). Despite significant differences among them, these three national festivals share common basis as expression of Brazilian traditional politics, society, and culture.